PERSEPSI PETANI TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN DI DESA SIDODADI KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA (The Perception of Farmers on The Performance Of Field Agricultural Instructors (PPL) In Si-dodadi Village, Sangkub Sub District, Bolaang Mongondow Utara Regency) - Oktafia Andriani; Agnes E. Loho; Audrey J. M. Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The existence of agricultural extension agents in Sidodadi Village is important because of the lack of knowledge and public awareness of the importance of this extension. The ability of farmers to obtain agricultural information and technology is a reflection of the confidence in the extension activities. Therefore, it is necessary to examine how the farmers' perceptions of the performance of field agricultural extension agents.The objective of this research is to determine farmers' perceptions of the performance of field agricultural instructors in Sidodadi Village, Sangkub Sub District, Bolaang Mongondow Utara Regency. This research was conducted from December 2019 to February 2020. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with 30 respondents using a questionnaire measured using a Likert scale. Secondary data obtained from books, journals, BPS (Central Statistics Agency), Village Offices and BPP (Agricultural Extension Center).Based on the results of the research, it can be concluded that the farmers' perceptions of the performance of the agricultural extension agents in Sidodadi Village are overall good. This is evidenced by the results of the interpretation of the value of farmers' perceptions on the performance of the extension workers, which was 84 percent.Keywords: Farmers' Perception, Agricultural Instructor Performance